2019
DOI: 10.1084/jem.20190736
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibodies against Mayaro virus require Fc effector functions for protective activity

Abstract: Despite causing outbreaks of fever and arthritis in multiple countries, no countermeasures exist against Mayaro virus (MAYV), an emerging mosquito-transmitted alphavirus. We generated 18 neutralizing mAbs against MAYV, 11 of which had “elite” activity that inhibited infection with EC50 values of <10 ng/ml. Antibodies with the greatest inhibitory capacity in cell culture mapped to epitopes near the fusion peptide of E1 and in domain B of the E2 glycoproteins. Unexpectedly, many of the elite neutralizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 54 publications
(88 reference statements)
4
90
1
Order By: Relevance
“…What is the effector function involved? Earnest et al (2019) showed that several of the protective nAbs promoted neutrophil and monocyte-dependent phagocytosis of E2-coated beads, as might be expected. Of note, the protective activities of IgG2a nAbs with similar neutralizing titers varied widely, suggesting a potentially rich area for further research to understand the underlying mechanisms involved.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…What is the effector function involved? Earnest et al (2019) showed that several of the protective nAbs promoted neutrophil and monocyte-dependent phagocytosis of E2-coated beads, as might be expected. Of note, the protective activities of IgG2a nAbs with similar neutralizing titers varied widely, suggesting a potentially rich area for further research to understand the underlying mechanisms involved.…”
supporting
confidence: 65%
“…In conclusion, Earnest et al (2019) describe a thorough study of Ab protection against an alphavirus in a mouse model (note that several different aspects of the study are not covered in this overview). It will be interesting to see the next stages of the work in terms of understanding the molecular origins of the observations made.…”
Section: Burtonmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a study by Santiago et al shows that neutralizing antibodies alone are not sufficient to prevent the occurrence of chronic arthritis [50]. Earnest and collaborators generated a series of neutralizing broad-spectrum mouse antibodies by the use of recombinant MAYV E2 protein [68] and showed their therapeutic utility against MAYV, thereby underscoring the importance that should be given to IgG subclasses and their effector functions. Diagram showing the probable dissemination of MAYV in humans, based on animal experiments and clinical data for similar alphaviruses.…”
Section: Clinical Manifestations and Pathogenesis Of Mayaro Fever Inmentioning
confidence: 99%
“…ADCC, ADCP, ….) have been shown to be required for antibody-mediated antiviral protection (Bournazos et al, 2014, 2019; Earnest et al, 2019; Fox et al, 2019; Gunn et al, 2018; Liu et al, 2017) whether and how FcγR engagement by antiviral mAbs affects the immunomodulatory properties of different FcγR-expressing cells (i.e. cytokines/chemokines secretion, activation markers expression, …) has been little studied.…”
Section: Introductionmentioning
confidence: 99%